Evaluation of wastewater treatment in a novel anoxic–aerobic algal–bacterial photobioreactor with biomass recycling through carbon and nitrogen mass balances. (September 2015) - Alcántara, Cynthia; Domínguez, Jesús M.; García, Dimas; Blanco, Saúl; Pérez, Rebeca; García-Encina, Pedro A.; Muñoz, Raúl
Graphical abstract: Highlights: A HRT of 2 days enabled TOC, IC and TN removal efficiencies of ≈80%. Light intensity and DOC governed the extent of N removal mechanisms. Biomass recycling resulted in fast settling flocs and low effluent TSS. Chlorella vulgaris and Proteobacteria were the main microorganisms in the system. N2 O emissions were far below the reported IPCC emission factor for WWTPs. Abstract: Algal–bacterial symbiosis, implemented in an innovative anoxic–aerobic photobioreactor configuration with biomass recycling, supported an efficient removal of total organic carbon (86–90%), inorganic carbon (57–98%) and total nitrogen (68–79%) during synthetic wastewater treatment at a hydraulic and sludge retention times of 2 days and 20 days, respectively. The availability of inorganic carbon in the photobioreactor, determined by its supply in the wastewater and microalgae activity, governed the extent of nitrogen removal by assimilation or nitrification–denitrification. Unexpectedly, nitrate production was negligible despite the high dissolved oxygen concentrations, denitrification being only based on nitrite reduction. Biomass recycling resulted in the enrichment of rapidly settling algal flocs, which supported effluent total suspended solid concentrations below the European Union maximum discharge limits. Finally, the maximum nitrous oxide emissions recorded were far below the emission factors reported for wastewater treatment plants, confirming the environmental sustainability of this innovative photobioreactor in terms of global warming impact.